2020
DOI: 10.5334/gh.873
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex Differences in Heart Rate Variability and Vagal Specific Patterns – Baependi Heart Study

Abstract: Background: Heart rate variability (HRV) is a noninvasive method for assessing autonomic function. Age, sex, and chronic conditions influence HRV. Objectives: Our aim was to evaluate HRV measures exploring differences by age, sex, and race in a sample from a rural area. Methods: Analytical sample (n = 1,287) included participants from the 2010 to 2016 evaluation period of the Baependi Heart Study, a family-based cohort in Brazil. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 20 publications
(60 reference statements)
3
31
2
1
Order By: Relevance
“…However, it should not be ignored that some of the HRV indices show a non-linear decreasing pattern as age increased. Results of two cohort studies in Brazil showed that parasympathetic associated time domain variables showed a U-shaped distribution and reversal increase between 60 and 70 years old, which were consistent with trend of the frequency domain parameters (HF) changing with age in our cohort (Almeida-Santos et al, 2016;Geovanini et al, 2020; Supplementary Table 4). Theoretically, the VLF band, which contributed mainly by parasympathetic nervous system activity, may display a reversal process in old-old patients (Berntson et al, 1997;Taylor et al, 1998).…”
Section: Discussionsupporting
confidence: 87%
“…However, it should not be ignored that some of the HRV indices show a non-linear decreasing pattern as age increased. Results of two cohort studies in Brazil showed that parasympathetic associated time domain variables showed a U-shaped distribution and reversal increase between 60 and 70 years old, which were consistent with trend of the frequency domain parameters (HF) changing with age in our cohort (Almeida-Santos et al, 2016;Geovanini et al, 2020; Supplementary Table 4). Theoretically, the VLF band, which contributed mainly by parasympathetic nervous system activity, may display a reversal process in old-old patients (Berntson et al, 1997;Taylor et al, 1998).…”
Section: Discussionsupporting
confidence: 87%
“…It is known that age and sex have an important impact on HRV [67][68][69][70][71]. Aging causes neuronal and structural modifications of the cardiorespiratory system leading to a decreased vagal tone [68,70].…”
Section: Discussionmentioning
confidence: 99%
“…Given the consistency between HRV values during pregnancy in this and others studies, it may be possible to identify normal ranges of values. Normal values for HRV measures may need to be adjusted for factors including age and different hormonal states across the perinatal period 77 , 78 . As an example for the latter from the literature, trait anxiety was found to be associated with greater decrease in HF and greater HF reactivity in the third trimester; along with greater increase in VLF compared with the second trimester 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%